A Survey of the Automated Irrigation Systems and the Proposal to Make the Irrigation System Intelligent - Jain, Srishti; Vani, KS (International Journal of Computer Sciences and Engineering, 2025)
Agriculture and farming are the key components and they contribute to the maximum in the income of any country. Farmers cannot depend on the rainfall for the crops cultivation. So, watering and monitoring of the crops becomes a critical issue. Less watering or more watering to the plants can be a serious issue and it may lead to the less yield of the crop. Also, farmers cannot be at the irrigation land all the time. So, we are proposing a design for automatic monitoring of the crops so that the system automatically understands the need of water to the plants and acts respectively. Also during heavy rains, we are proposing to drain out the excess water in the fields so that it will not affect the plants yield. We are also proposing to apply artificial intelligence to the irrigation system. By this the plants will be continuously monitored for any diseases affecting the crops and any changes in the quality of the crops which will be immediately notified to the farmer. Also planning to detect the budding weeds around the crops. In this paper the survey of different papers on automated irrigation system has been presented with their advantages, limitations and their future scope.